Monotropein inhibits epithelial–mesenchymal transition in chronic colitis via the mTOR/P70S6K pathway - Chen, Yuanfan; Liu, Jiaying; Zhong, Shaowen; Zhang, Tianwu; Yuan, Jin; Zhang, Jing; Chen, Ying; Liang, Jian; Chen, Yonger; Hou, Shaozhen; Huang, Haiyang; Gao, Jie (Frontiers in Pharmacology, 2025)
IntroductionPatients with chronic colitis are at risk of developing intestinal fibrosis through epithelial–mesenchymal transition (EMT). Monotropein (MON) is the main active ingredient in the traditional Chinese medicine Morinda officinalis How. It has been reported that monotropein can improve ulcerative colitis, but the mechanism remains unclear. However, whether monotropein can improve chronic colitis-associated intestinal fibrosis remains unknown. The study aimed to investigate the effect of monotropein on EMT in chronic colitis and its underlying mechanism.MethodsThe mice chronic colitis model was induced by dextran sodium sulfate (DSS). Cytokines were detected by ELISA. Concentrations of fluorescein isothiocyanate dextran (FITC-Dextran) in serum were detected using a fluorescein microplate analyzer. Intestinal tight junction proteins were detected by immunofluorescence. EMT marker proteins were detected by immunohistochemistry. Transforming growth factor-β1 (TGF-β1) was used to induce EMT in IEC-6 cells. Western blot, real-time quantitative PCR, and immunofluorescence were used to test the inhibitory effect of monotropein on the development of EMT and explore its mechanism.ResultsResults showed that monotropein significantly improved colonic injury and inhibited the expression of colonic tissue EMT marker protein. In addition, molecular docking and molecular dynamics (MD) simulation, cellular thermal shift assay (CETSA), and drug affinity responsive target stability (DARTS) assay validated monotropein targeting of mTOR. Monotropein inhibited TGF-β1-induced EMT in IEC-6 cells, inhibited the phosphorylation of mTOR and its downstream proteins, and increased the autophagy activity in chronic colitis mice and IEC-6 cells.DiscussionThe study indicates that monotropein inhibits the development of EMT in DSS-induced chronic colitis mice and TGF-β1-induced IEC-6 cells. Its inhibitory effect on EMT is associated with the mTOR/P70S6K pathway.